Refinement of cooking oil using activated carbon from coconut shell and zeolite - Jumiati, Ety (Universitas Gadjah Mada, 2024)
Bulk cooking oil is obtained from traditional markets and and relatively has a characteristic color that tends to be brownish and unclear; cooking oil has been repeatedly used after frying, resulting in physical changes such as darkening, thickening, and foaming. If bulk cooking oil is repeatedly used for frying, it can be detrimental to health as it may accumulate saturated fatty acids in the oil. This condition prompted the search for solutions to purify bulk cooking oil and use cooking oil using processed zeolite and coconut shell-activated carbon as adsorbents to improve the quality of cooking oil. This research utilizes an experimental-quantitative method. Variations in composition include sample A (bulk cooking oil: 75% and processed natural zeolite: 25%), sample B (bulk cooking oil: 75% and coconut shell activated carbon: 25%), sample C (used cooking oil: 75% and processed natural zeolite: 25%), and sample D (used cooking oil: 75% and coconut shell activated carbon: 25%). The research results on the quality of coconut shell activated carbon obtain moisture content of 13.2%, ash content of 2.1%, volatile matter content of 17.9%, and carbon content of 80.0%, which meets the SNI 06-3730-1995 standard. Meanwhile, the quality results of cooking oil after the purification process obtain moisture content values of 0.09-0.10%, free fatty acid values of 0.14-0.30%, and normal color that does not exceed the maximum standard required by SNI 7709:2019 with a percentage reduction in moisture content of 0-60% and free fatty acids of 0-63.41%.